Biomimetic Fe7S8/Carbon electrocatalyst from [FeFe]‐Hydrogenase for improving pH‐Universal electrocatalytic hydrogen production - Dohun Kim; Subramani Surendran; Sejin Im; Jaehyoung Lim; Kyoungsuk Jin; Ki Tae Nam; Uk Sim (Aggregate, 2024)
Abstract Efficient and cost‐effective electrocatalysts that can operate across a wide range of pH conditions are essential for green hydrogen production. Inspired by biological systems, Fe7S8 nanoparticles incorporated on polydopamine matrix electrocatalyst were synthesized by co‐precipitation and annealing process. The resulting Fe7S8/C electrocatalyst possesses a three‐dimensional structure and exhibits enhanced electrocatalytic performance for hydrogen production across various pH conditions. Notably, the Fe7S8/C electrocatalyst demonstrates exceptional activity, achieving low overpotentials of 90.6, 45.9, and 107.4 mV in acidic, neutral, and alkaline environments, respectively. Electrochemical impedance spectroscopy reveals that Fe7S8/C exhibits the lowest charge transfer resistance under neutral conditions, indicating an improved proton‐coupled electron transfer process. Continuous‐wave electron paramagnetic resonance results confirm a change in the valence state of Fe from 3+ to 1+ during the hydrogen evolution reaction (HER). These findings closely resemble the behavior of natural [FeFe]‐hydrogenase, known for its superior hydrogen production in neutral conditions. The remarkable performance of our Fe7S8/C electrocatalyst opens up new possibilities for utilizing bioinspired materials as catalysts for the HER.